Analisis risiko kesehatan dan keselamatan kerja pada pekerjaan konstruksi pangadaan dan pemasangan intelligent transportation system Kota Medan - Raja, Erwin Febrian Nadeak; Kalsum; Sinaga, Mhd. Makmur; Silaban, Gerry (Talenta Publisher, 2023)
The installation of Intelligent Transportation System that serves to integrate road users, transportation systems and vehicles through information systems and communication technologies. Therefore, the purpose of this study is to identify hazards and risk analysis of work accidents in the installation of Intelligent Transportation System Medan. This type of research uses qualitative research design to identify hazards and perform risk level analysis on Intelligent Transportation System (ITS) installations using the AS/NZS 4360:2004 framework on risk management, was conducted at Gatsu Sei Wampu, Mayestik, and Merdeka Square intersection in February 2023 – completed. Data analysis methods, namely domain analysis. Based on the results of the study obtained the potential hazards of Occupational Safety and health contained in the installation location of The Intelligent Transportation System (ITS) in the form of injury or cuts, hit by vehicles, noise, electric shock, falling, buried, inhaled particles of material, material crushed and falling from a height. Hazard Control of Occupational Safety and health risks that can be done is testing the tools to be used, preparation of workers 'competence and health, provision of PPE for workers, provision of safe areas and traffic officers, implementing SOPs and installing K3 signs. Expected for all workers at PT. Means of terrain traffic to be able to implement safe behavior while working by always using PPE such as helmets, shoes, gloves, masks and vests as well as other PPE such as earmuffs/earplugs if the noise exceeds the threshold value (NAB).